Investigation of the impact of brewing parameters on toxic element and rare earth element contamination in oolong tea - Wu, Sixuan; Peng, Ziming; Ou, Yijun; Mhungu, Florence; Wang, Yanyan; Zhang, Yuhua; Liu, Lan; Lei, Jiangbo; Huang, Lili; Peng, Rongfei; Bai, Zhijun; Zhang, Weiwei (Frontiers in Nutrition, 2025)
IntroductionWith the growing consumption of oolong tea, concerns regarding the leaching of toxic elements and rare earth elements (REEs) during brewing necessitate investigation.MethodsWe analyzed 108 oolong teas of diverse origins and varieties. The concentrations of six toxic elements (including Pb, Cd, Al) and fifteen REEs were measured by ICP-MS. The effects of water temperature (90°C, 100°C) and brewing time (5 seconds to 2 hours) on leaching rates were systematically examined.ResultsHigh temperature and long brewing time significantly increased (P<0.05) the leaching of most elements. Tieguanyin tea contained the highest levels of Pb, Al, and REEs. Samples from Fujian province significantly exceeded safety standards for Pb and Al. Anomalously, the leaching rate of Cd was lower at 100°C than at 90°C, while the release of scandium (Sc) increased with temperature.DiscussionThis study reveals that brewing conditions are critical for elemental migration. To minimize the intake of harmful substances, consumers are advised to shorten the brewing time. We also call for strengthened regulatory standards for toxic elements and REEs in tea. These findings provide a scientific basis for guiding safe tea consumption practices.